Sensitive voltammetric method for determination of chemotherapeutic drug methotrexate using liquid mercury free silver solid amalgam electrode - Bandžuchová, Lenka; Šelešovská, Renáta; Chýlková, Jaromíra (University of Pardubice, 2014)
Voltammetric behaviour of a wide-spread used chemotherapeutic drug methotrexate (MTX) was investigated on a polished silver solid amalgam electrode (p-AgSAE) employing various voltammetric methods like cyclic voltammetry, direct current voltammetry and differential pulse voltammetry. It was found that MTX provided two reduction and one oxidation peak in an acidic medium, and the positively situated reduction signal (Ep = –340 mV), due its favorable analytical properties, was studied more in detail. 0.05 mol l–1 acetate buffer of pH 5 was selected as an optimum medium for monitoring of the MTX reduction on p-AgSAE. Operating parameters of differential pulse voltammetry were optimized and proposed voltammetric method provided high repeatability (relative standard deviation of 11 repeated measurements at concentration level of methotrexate of 1×10–7 mol l–1 equaled to 1.7 %), linear concentration range from 5×10–10 to 3×10–6 mol l–1 and low limit of detection (LD = 1.5×10–10 mol l–1). The applicability of proposed method was verified by analysis of real sample of chemotherapeutic preparation.